A new clustering technique based on replication for MANET routing protocols - Salma S. Mohammed; A. I. Abd-Elfattah; Mohamed A. Mohamed (Universitas Ahmad Dahlan, 2020)
The cluster head nodes in most mobile ad hoc networks (MANET) clustering protocols take on an extraordinary role in managing routing information. The reliability, efficiency and scalability of the clustering in MANET will ultimately be dramatically impacted. In this work we establish a new approach to form the clusters in MANET called the square cluster-based routing protocol (SCBRP). That protocol is based on the theory of replication. The goal of the protocol is to achieve reliability, availability and scalability with in the MANET. The proposed protocol is evaluated by caring the performance analysis using the NS-3 simulator. The performance shows 50% improvementin data delivering ratio in large network size, also shows an improvement in network stability and availability which is reflected in energy consumption measurements and increase in the system lifetime to 20%.